2020
DOI: 10.1016/j.jtcme.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcerogenic effects of Celosia trigyna plant extracts on ethanol-induced gastric ulcer in adult Wistar rats

Abstract: Background and aim Gastric ulcer is a chronic disease and serious health issue. Celosia trigyna is a medicinal plant used traditionally for wound healing. This study aimed to isolate the bioactive compounds from Celosia trigyna and to investigate the in vitro and in vivo anti-ulcerogenic effects of the extract s on ethanol-induced gastric ulcer on adult Wistar rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…[3,29,32,37] In the current study, rats pre-nourished with gold nanoparticle enhanced construction of stomach mucosa increase wide improvement protein concentration in gastric secretions. [38,39] Significances of the present exercise were similar with other amendments quantity gastroprotective and antiulcer achievement gold nanoparticle and herbal composites. [4,40,41] Pre-feeding with the gold nanoparticle, challengingly impassable gastric acid likewise takeover stomach injury in rats forced feeding ethanol, characteristic gastro-protective effect gold nanoparticle easy relatively protection of gastric wall.…”
Section: Discussionsupporting
confidence: 67%
“…[3,29,32,37] In the current study, rats pre-nourished with gold nanoparticle enhanced construction of stomach mucosa increase wide improvement protein concentration in gastric secretions. [38,39] Significances of the present exercise were similar with other amendments quantity gastroprotective and antiulcer achievement gold nanoparticle and herbal composites. [4,40,41] Pre-feeding with the gold nanoparticle, challengingly impassable gastric acid likewise takeover stomach injury in rats forced feeding ethanol, characteristic gastro-protective effect gold nanoparticle easy relatively protection of gastric wall.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, several academics using medicinal plants or their active ingredients reported a flatting of the gastric mucosa and the anti-ulcer effects of stomach mucosa in rats; indeed, a previous study has shown the anti-ulcer effects of Celosia trigyna in 50 mg/kg dosage against ethanol-induced ulcers in rats. Furthermore, another research team have demonstrated Monolluma quadrangula to be an anti-ulcer medicinal plant after showing its efficacy in 150 or 300 mg/kg dosage against ethanol-induced ulcers in rats [7,50].…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol is a necrotizing agent that induces oxidative stress and stomach mucosal ulceration through the generation of highly cytotoxic free radicals [4,5]. Oxygen-derived free radical species induced by ethanol administration are among the mucosal invasive factors responsible for peptic ulcers by causing oxidative damage to gastric mucosal cells [6,7]. The exogenous and endogenous active oxygen and oxidants (superoxide dismutase and single oxygen peroxidase) can easily cause damage to gastric mucosal linings.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopic scores were calculated, based on the following parameters: edema or hemorrhage, loss of mucosal folding, and mucosal discoloration. The number of ulcers were counted, and ulcer severity was determined 22 23 . Below is the ulcer score: 0=Normal colored stomach, 0.5=Red coloration, 1.0=Spot ulcers, 1.5=Hemorrhagic streaks, 2.0=Deep ulcer, and 3.0=Perforations.…”
Section: Methodsmentioning
confidence: 99%